Thermoanalytical study of heavier trivalent lanthanides fumarates - Alves, F. S.; Bembo, L. H.; Caires, F. J. [UNESP]; Ionashiro, E. Y. (Springer Nature, 2013)
Solid-state heavier lanthanides fumarates compounds have been synthesized, and the compounds were characterized by employing simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), TG coupled to FTIR, elemental analysis, and complexometry. On heating, the dehydration occurs in a single and two consecutive steps and the thermal decomposition of the anhydrous compounds occurs in consecutive and/or overlapping steps, with formation of the respective oxides: Tb4O7 and Ln2O3 (Ln=Dy to Lu). The results also led to information about composition, thermal behavior, and the type of coordination of the isolated compounds. © 2012 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Fumarate; Heavier lanthanides; Thermal behavior; Anhydrous compounds; Complexometry; Fumarates; Isolated compounds; Thermal behaviors; Thermoanalytical study; Trivalent lanthanides; Decomposition; Differential scanning calorimetry; Differential thermal analysis; Fourier transform infrared spectroscopy; Rare earth elements; Thermogravimetric analysis; Dysprosium compounds